Highly efficient sulfonic/carboxylic dual-acid synergistic catalysis for esterification enabled by sulfur-rich graphene oxide - Zhang, Honglei; Luo, Xiang; Shi, Kaiqi; Wu, Tao; He, Feng; Zhou, Shoubin; Chen, George Z.; Peng, Chuang (Wiley, 2017)
A new sulfonic/carboxylic dual-acid catalyst based on sulfur-rich graphene oxide (GO-S) was readily prepared and used as a highly efficient and reusable solid acid catalyst toward the esterification of oleic acid with methanol for biodiesel production. Higher yields of methyl oleate (98 %) and over 3 times higher turnover frequencies (TOFs) were observed for the GO-S dual-acid catalyst, compared to liquid sulfuric acid or other carbon-based solid acid catalysts. The “acidity” of sulfonic acid groups was enhanced by the addition of carboxylic acid groups as the combination of the two acids enhances their inherent activity by associative interaction.